2020
DOI: 10.4149/gpb_2020021
|View full text |Cite
|
Sign up to set email alerts
|

miR-129-5p ameliorates ischemia-reperfusion injury by targeting HMGB1 in myocardium

Abstract: Globally, acute myocardial infarction (AMI) is a serious condition affecting millions of individuals. While AMI therapy improves blood flow during surgery, reperfusion-induced injury may also occur, leading to secondary cardiac damage or even death. Here, we investigated miR-129-5p in myocardial ischemia-reperfusion (I/R) injury in rats, to explore reperfusion-related molecular mechanisms in myocardium. We used Sprague Dawley rats to establish a myocardial I/R model, with agomiR-129-5p injection, and used rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, prior to finding such an innovative method for subsequent treatment of AMI just after the primary PCI procedure, the pathophysiological mechanism of myocardial damage/death prior to and after primary PCI should be more thoroughly clarified ( 4 ). According to the reports from basic and clinical research ( 1 , 4 , 17 24 ), it is reasonable to believe that at least six cardinal reasons for myocardial damage: (1) myocardial necrosis due to complete loss of the blood supply prior to primary PCI, (2) ischemia-reperfusion injury, (3) AMI-elicited rigorous inflammatory reaction, (4) immune hyper-reactivity (i.e., overwhelming immune response), (5) inflammatory cell infiltration and proinflammatory cytokine release in infarct/peri-infarct areas, and (6) generations of reactive oxygen species (ROS)/free radicals which cause oxidative stress after AMI.…”
Section: Introductionmentioning
confidence: 99%
“…However, prior to finding such an innovative method for subsequent treatment of AMI just after the primary PCI procedure, the pathophysiological mechanism of myocardial damage/death prior to and after primary PCI should be more thoroughly clarified ( 4 ). According to the reports from basic and clinical research ( 1 , 4 , 17 24 ), it is reasonable to believe that at least six cardinal reasons for myocardial damage: (1) myocardial necrosis due to complete loss of the blood supply prior to primary PCI, (2) ischemia-reperfusion injury, (3) AMI-elicited rigorous inflammatory reaction, (4) immune hyper-reactivity (i.e., overwhelming immune response), (5) inflammatory cell infiltration and proinflammatory cytokine release in infarct/peri-infarct areas, and (6) generations of reactive oxygen species (ROS)/free radicals which cause oxidative stress after AMI.…”
Section: Introductionmentioning
confidence: 99%
“…miR-129-5p plays important roles in cancer by either promoting or inhibiting tumorigenesis through regulating a variety of downstream targets and pathways 61, 62 . Several studies have shown that miR-129-5p protects adult hearts from ischemia/reperfusion injuries 63, 64 , while another study demonstrated that treating cultured H9c2 cardiomyocytes with HDAC pan-inhibitor Trichostatin A results in decreased cardiomyocyte proliferation with enhanced miR-129-5p expression 65 . This is consistent with our current findings in the developing endocardium (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our study, miR-129-5p alleviates myocardial injury after ischemia/reperfusion ( 17 ). miR-129-5p ameliorated ischemia-reperfusion injury by targeting HMGB1 in myocardium ( 18 ). All these results indicate that miR-129-5p play a positive effect on myocardial I/R injury.…”
Section: Discussionmentioning
confidence: 99%